What traits of collaboration networks are associated with project success? The case of two CGIAR agricultural research programs for development - Plex Sulá, A.I.; De Col, Valentina; Etherton, B.A.; Yanru Xing; Agarwal, A.; Ramić, L.; Bonaiuti, Enrico; Friedmann, M.; Proietti, Claudio; Thiele, Graham; Garrett, Karen A. (Elsevier, 2024)
CONTEXT Understanding research collaboration in diverse scientific communities is key to building global agricultural research systems that support the UN Sustainable Development Goals. Characterizing collaboration patterns can inform decisions to enhance the structure and dynamics of research programs.